Meaning-Making Process and Aesthetic Response in Sylvia Plath’s Selected Poems - Huma Ahmad; Sadaf Khalid (Journal of Management Practices, Humanities and Social Sciences, 2022)
This paper intends to investigate the meaning-making process in Sylvia Plath's poetry by employing Wolfgang's theory of Aesthetic Reader Response. Since female writing is characterized by a strong emotional appeal, especially for a female reader, the research is an attempt to explore the meaning-making process in Plath's poetry that how and why it (female writing) is appealing to the female reader in particular, and to the male reader in general. The analysis is anchored within Wolfgang Iser's theory of Aesthetic Reader Response. His theory postulates that the importance of literary work does not entirely lie in the meaning that the text beholds within it; instead, it depends on the interaction of the text with the reader that is helpful in the establishment of a new meaning. The present paper attempts to reveal this ideal relationship between a female poet and a female reader in the meaning-making process. The research uses a descriptive cum analytical method. Since the study intends to explore and investigate the aesthetic appeal and response that the profoundly emotional poetry of Sylvia evokes in the reader, the linguistic and stylistic choices will remain the focus. So, the research, at times, falls into the category of stylistic analysis. This article demonstrates how a female writer/poet offers a crucial understanding of the relationship between 'ecriture feminine' and the emergence of meaning. The research will provide future researchers with an opportunity to explore the meaning-making process in fictional work by female authors from the standpoint of female readers.